PERMASALAHAN DAFTAR PEMILIH TETAP PADA PEMILIHAN BUPATI DAN WAKIL BUPATI SAMPANG TAHUN 2018 DALAM PERSPEKTIF INTEGRITAS PEMILU - Dina (Bahasa Indonesia, 2019)
Updating voter data in the 2018 Sampang Regency Election leaves a problem that caused the Constitutional Court decision ordering the General Election Commission (KPU) to conduct a re-voting at all polling stations in Sampang. The Court considered that the Permanent Voter List (DPT) determined by the Sampang Regency KPU was invalid and illogical when compared to the DAK2 received by the KPU in the first semester of 2017, amounting to 844,872 while the DPT was 803,499, this meant that the number of permanent voters was 95% of the population. This research was conducted to examine the issue of updating voter data in Sampang District in the 2018 regional election and how efforts could be made to resolve it. The method used in this research is qualitative descriptive through in-depth interviews with member of KPU Kabupaten Sampang, PPK and Dispendukcapil Kabupaten Sampang. Through the data research result can be described that the problem of voter registration in Sampang are unsynchronous regulations governing the source of voter data, PPDP is not professional in carrying out their duties due to pressure or influence from the local elite, lack of community participation in checking voter data, The updating officer still does not understand the shifting of the voter database from de facto to de jure which causes the emergence of double data between polling stations, villages, and districts, the lack of supervision and monitoring in the voter data updating process due to the inaccurate voter data.